1997
DOI: 10.1097/00005392-199701000-00065
|View full text |Cite
|
Sign up to set email alerts
|

Extraprostatic Production of Prostate Specific Antigen is Under Hormonal Control

Abstract: Our data demonstrate that extraprostatic PSA production is under androgen control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
0
10
0
2
Order By: Relevance
“…The 42 patients with prostate cancer underwent radical prostatectomy and there was no difference in urinary PSA between lower (4-6) and higher (7)(8)(9) Gleason scores (median 49 ng/mL and 70 ng/mL, respectively; p = 0.40). The staging capacity was assessed and patients with stage T1 (n = 5) and T2 (n = 21) tumours had similar serum and urinary PSA as well as PSA ratios (p > 0.20); therefore, they were pooled together to be compared with stage T3 tumours.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The 42 patients with prostate cancer underwent radical prostatectomy and there was no difference in urinary PSA between lower (4-6) and higher (7)(8)(9) Gleason scores (median 49 ng/mL and 70 ng/mL, respectively; p = 0.40). The staging capacity was assessed and patients with stage T1 (n = 5) and T2 (n = 21) tumours had similar serum and urinary PSA as well as PSA ratios (p > 0.20); therefore, they were pooled together to be compared with stage T3 tumours.…”
Section: Resultsmentioning
confidence: 93%
“…Over the years, PSA has been measured on different samples: in urine voided before and after prostate massage, 3,4 in first-voided urine, [4][5][6] in single midstream sample of urine [7][8][9][10] and in 24-hour urine specimens. [11][12][13] The fact that a urine specimen contains more PSA certainly appears to be an advantageous issue in terms of method of choice for PSA measurement.…”
mentioning
confidence: 99%
“…Androgenic therapies established for female to male transsexuals led to elevated levels of serum PSA comparable with the results of increased urinary PSA levels secondary to long‐term testosterone treatments used in the same group of patients 14–16 . All those data concluded that there is a link between increased androgen levels and PSA values measured in serum or urine.…”
Section: Introductionmentioning
confidence: 73%
“…However, estrogen may impair indirectly the androgen‐induced PSA production 9,27,31 . Both serum and urine PSA levels are also reported to be elevated in response to long‐term androgenic (Testosterone) therapy in female‐to‐male transsexuals 14,16 . Additionally, a number of authors such as Melegos and Escobar‐Morrale concluded that hirsute females with hyperandrogenism presented clearly elevated serum PSA levels when compared to control cases 9,32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study documented that the concentration of PSA in cord blood is higher in case of higher gestational age, male baby and operative delivery and explained that higher progesterone levels in prenatal maternal blood having male babies may be responsible for the higher cord blood PSA while operative interventions like caesarian section or forceps delivery results in much more stress and strain compared to normal vaginal delivery, with subsequent increase in levels of adrenal glucocorticoids, and therefore, higher cord blood PSA [54]. Breul et al [55] reported that female patients receiving Testosterone supplementation has PSA levels comparable with that of men with significantly elevated urinary PSA levels presumably as a result of increased production of PSA by the periurethral glands. These studies reveal that PSA production is upregulated by androgens.…”
Section: Psa In Femalesmentioning
confidence: 99%